2023
DOI: 10.1007/s00018-023-04777-w
|View full text |Cite
|
Sign up to set email alerts
|

Atrial natriuretic peptide stimulates autophagy/mitophagy and improves mitochondrial function in chronic heart failure

Abstract: Mitochondrial dysfunction, causing increased reactive oxygen species (ROS) production, is a molecular feature of heart failure (HF). A defective antioxidant response and mitophagic flux were reported in circulating leucocytes of patients with chronic HF and reduced ejection fraction (HFrEF). Atrial natriuretic peptide (ANP) exerts many cardiac beneficial effects, including the ability to protect cardiomyocytes by promoting autophagy. We tested the impact of ANP on autophagy/mitophagy, altered mitochondrial str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Based on previous evidence that abnormal mitochondrial structure and function are associated with altered mitophagy and increased oxidative stress in HF with reduced ejection fraction (HFrEF) [ 59 ], a recent study tested the impact of ANP (able to stimulate autophagy/mitophagy in cardiomyocytes [ 105 ]) in HFrEF patients by both ex vivo and in vivo approaches [ 106 ]. In the ex vivo study, PBMCs isolated from HFrEF patients were directly exposed to αANP.…”
Section: Mitochondria As Potential Therapeutic Targets In Hfmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous evidence that abnormal mitochondrial structure and function are associated with altered mitophagy and increased oxidative stress in HF with reduced ejection fraction (HFrEF) [ 59 ], a recent study tested the impact of ANP (able to stimulate autophagy/mitophagy in cardiomyocytes [ 105 ]) in HFrEF patients by both ex vivo and in vivo approaches [ 106 ]. In the ex vivo study, PBMCs isolated from HFrEF patients were directly exposed to αANP.…”
Section: Mitochondria As Potential Therapeutic Targets In Hfmentioning
confidence: 99%
“…In the ex vivo study, PBMCs isolated from HFrEF patients were directly exposed to αANP. The in vivo study included HFrEF patients who received a treatment with sacubitril/valsartan, a first-line pharmacological therapy consisting in the association of the type 1 angiotensin II receptor and neprilysin inhibitors, the latter causing an increase in NPs, mainly αANP [ 106 ]. Both the ex vivo direct exposure to αANP and the higher αANP level upon in vivo treatment were able to restore mitochondrial membrane potential, to stimulate the autophagic process with an increase in the mitochondrial mass index, to reduce mitochondrial damage with an increased IMM/OMM index, and to decrease ROS levels [ 106 ].…”
Section: Mitochondria As Potential Therapeutic Targets In Hfmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative damage contributes to impairment of the electron transport chain, to mitochondrial uncoupling, and finally to bioenergetic dysfunction, which promotes cell death. [ 38 , 39 ]. In addition, shear stress due to hypertension is associated with the activation of different biological pathways, such as PKC epsilon, c-Jun N-terminal kinase (JNK), MAP kinase, and p53, contributing to atherosclerotic plaque progression and a further worsening of endothelial function [ 40 , 41 , 42 ], contributing to the progression to HFrEF ( Figure 1 ).…”
Section: Hypertension and Heart Failure Phenotypesmentioning
confidence: 99%
“…The ANP signaling mechanism in trophoblasts is not fully understood. In the heart, ANP modulates autophagy, a process of regulating cellular function depending on pathophysiological conditions [135,136]. In a recent study in human trophoblasts and chorionic villi, a molecular mechanism has been suggested, in which ANP activates NPR-A and subsequent adenosine 5 -monophosphate-activated protein kinase (AMPK) and the mammalian target of rapamycin complex 1 (mTORC1) signaling to inhibit autophagy and induce protein kinase N3 (PKN3) expression, thereby increasing metalloproteinase expression and trophoblast invasiveness [134] (Figure 4).…”
Section: Trophoblast Invasionmentioning
confidence: 99%